The Glycan Structure of T. cruzi mucins Depends on the Host. Insights on the Chameleonic Galactose - Giorgi, María Eugenia (2020)
Trypanosoma cruzi, the protozoa that causes Chagas disease in humans, is transmitted by insects from the Reduviidae family. The parasite has developed the ability to change the structure of the surface molecules, depending on the host. Among them, the mucins are the most abundant glycoproteins. Structural studies have focused on the epimastigotes and metacyclic trypomastigotes that colonize the insect, and on the mammal trypomastigotes. The carbohydrate in the mucins fulfills crucial functions, the most important of which being the accepting of sialic acid from the host, a process catalyzed by the unique parasite trans-sialidase. The sialylation of the parasite influences the immune response on infection. The O-linked sugars have characteristics that differentiate them from human mucins. One of them is the linkage to the polypeptide chain by the hexosamine, GlcNAc, instead of GalNAc. The main monosaccharide in the mucins oligosaccharides is galactose, and this may be present in three configurations. Whereas β-d-galactopyranose (β-Galp) was found in the insect and the human stages of Trypanosoma cruzi, β-d-galactofuranose (β-Galf) is present only in the mucins of some strains of epimastigotes and α-d-galactopyranose (α-Galp) characterizes the mucins of the bloodstream trypomastigotes. The two last configurations confer high antigenic properties. In this review we discuss the different structures found and we pose the questions that still need investigation on the exchange of the configurations of galactose.